Evaluation of vegetation types in the West Zagros - ATENA ESLAMI FAROUJI; HAMED KHODAYARI (Biodiversitas Journal of Biological Diversity, 2016)
Farouji AE, Khodayari H. 2016. Evaluation of vegetation types in the West Zagros (Beiranshahr region as a case study), inLorestan Province, Iran. Biodiversita 17: 1-10. The accurate identification of plant communities and their distribution are classical tools for mapping and classification of plants. Plants are strongly sensitive against changing environmental conditions. Moreover, Iran has a special position in Asia which has been creating a diverse ecosystem. Close floristic studies are necessary for precise determination of diversity and uniformity. To determine plant species in different vegetation types in Beiran shahr region, modified multi-scale Whittaker plots were constructed. This studied area was about 20000 ha and located in Northwest to Southwest of Iran. Eighty-nine plots were made in different longitude and latitudes. The minimum and maximum heights were 1101 and 2489 m asl., respectively. Within each modified multi-scale plots, each species was explored. Of 608 species, 498 and 97 are belonging to dicotyledons and monocotyledons,Â and remained 13 species were Pteridophytes. As measured, Therophyte and Champhyte are the dominant and recessive form of life in studied area. Based on species of each plot and subplots, mean Jaccard's coefficient, number of unique species and mean unique species/plot were estimated for each vegetation type. It is obvious that there is a clear correlation between Slopes of the species-log area curve and Mean number of unique species per plot.